EFEKTIVITAS PENGGUANAAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMNET BERBANTUAN APLIKASI KAHOOT TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Anjani, Safira; Rahmawati, Septina; Manggalastawa; Cahya Rohim, Dhina; Awalludin Nugraha, Yoga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the improvement of learning outcomes, measure the effectiveness, and determine the classical completeness of students in Science and Social Science (IPAS) learning using the Teams Games Tournament (TGT) model assisted by the Kahoot application. The research was motivated by the low student achievement in the topic of the photosynthesis process, attributed to the u se of conventional teacher-centered teaching methods with minimal interactive media. A quantitative approach with a quasi-experimental nonequivalent pretest-posttest control group design was employed. The sample consisted of 26 fourth-grade students from SD 3 Pedawang (experimental class) and 24 fourth-grade students from SD 1 Pedawang (control class). Data were collected through observation, interviews, tests, and documentation, and analyzed using normality and homogeneity tests, paired sample t-test, independent sample t-test, N-Gain, and classical completeness analysis. The results showed a significant difference between the experimental and control classes (Sig. 0.005 < 0.05). The experimental class's average score increased from 52.50 to 84.23, while the control class improved from 46.67 to 72.71. The N-Gain score for the experimental class was 63.71% (moderately effective), compared to 46.99% (less effective) for the control class. Classical completeness reached 100% in the experimental class and 66.67% in the control class. In conclusion, the TGT model assisted by Kahoot is proven effective in improving fourth-grade students' IPAS learning outcomes, outperforming conventional methods, and fulfilling the criteria for classical completeness.